2021
DOI: 10.3390/agriculture11060541
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pearl Millet and Sorghum–Sudangrass Pastures during the Frost-Prone Autumn for Growing Beef Cattle in Semiarid Region

Abstract: Sorghum–sudangrass (Sorghum bicolor × S. sudanense (Piper) Stapf.) and pearl millet (Pennisetum glaucum (L.) R. Br.) provide adequate nutritive value for growing beef cattle; however, unlike pearl millet, sorghum–sudangrass produces hydrocyanic acid (which is toxic to livestock) when frosted. Forage yield, nutritive value, and weight gain of growing cattle grazing sorghum–sudangrass and pearl millet were compared during the frost-prone autumns of 2013 and 2014, at New Mexico State University’s Rex E. Kirksey A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
4
2
Order By: Relevance
“…They were also greater than those measured by Machicek et al [2] for PG harvested 90 DAP and by Oskey et al [18] for a first harvest monoculture PG at early heading. The PG DM yields measured in this study as monoculture and in mixtures (Table 3) were slightly greater than those for monoculture PG reported by others [9,16]. Yields reported by [9] for PG were planted later than the present study and harvested at the season's end about 4 months after planting.…”
Section: Pearl Millet Dm Yield and Nutritive Valuecontrasting
confidence: 71%
See 2 more Smart Citations
“…They were also greater than those measured by Machicek et al [2] for PG harvested 90 DAP and by Oskey et al [18] for a first harvest monoculture PG at early heading. The PG DM yields measured in this study as monoculture and in mixtures (Table 3) were slightly greater than those for monoculture PG reported by others [9,16]. Yields reported by [9] for PG were planted later than the present study and harvested at the season's end about 4 months after planting.…”
Section: Pearl Millet Dm Yield and Nutritive Valuecontrasting
confidence: 71%
“…Br.) [3,[6][7][8][9][10]. Both species are well adapted to semiarid regions and require less water than maize (Zea mays), which is generally grown for silage [3,7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, winter cereals can still provide valuable forage from Dec-Feb to fill the gap between autumn and spring [26]. Lauriault et al [30] suggested that using warm-season annual grass forages, such as pearl millet (Pennisetum glaucum (L.) R. Br.…”
Section: Grazing Period Total Animal Gain Andaverage Daily Gainsmentioning
confidence: 99%
“…Similarly, the cows fed with pearl millet silage consumed more dry matter than those fed with sorghum silage or tropical corn silage ( Amer and Mustafa, 2010 ). Most recently, Lauriault et al (2021) observed that both pearl millet and sorghum-sudangrass produced equal dry matter yield at single cut forage, and the pearl millet crop provided greater average daily gains than sorghum–sudangrass in beef when both have the same levels of nutritive value. In another livestock performance study by Vinutha et al (2021) , Nellore ram lambs fed with pearl millet silage showed increased digestibility than those fed with sorghum silage harvested at 76 days after sowing.…”
Section: Introductionmentioning
confidence: 99%